2022
DOI: 10.1097/aud.0000000000001270
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Evidence-Based Military Auditory Fitness-for-Duty Standard Based on the 80-Word Modified Rhyme Test

Abstract: Objectives: One important function of military audiology is to conduct evaluations of service members (SMs) with hearing loss to ensure they are fit for deployment in dangerous operational environments. The objective of this study was to establish evidence-based auditory fitness-for-duty criteria based on speech-in-noise performance on the 80- and 160-word clinical versions of the Modified Rhyme Test (MRT80 and MRT160). Design: Approximately 2400 SMs with various levels of hearing loss were recruited to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Participants included in this study were recruited as part of a larger research study examining suprathreshold auditory function in US SMs, in which participants answer survey questions and complete auditory tasks such as speech recognition in noise (Brungart et al, 2023;Davidson et al, 2023). A total of 3836 United States SMs (546 female, 3290 male) between the ages of 18-57 years (mean (SD) = 28.4 (7.28)) were recruited for this study.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants included in this study were recruited as part of a larger research study examining suprathreshold auditory function in US SMs, in which participants answer survey questions and complete auditory tasks such as speech recognition in noise (Brungart et al, 2023;Davidson et al, 2023). A total of 3836 United States SMs (546 female, 3290 male) between the ages of 18-57 years (mean (SD) = 28.4 (7.28)) were recruited for this study.…”
Section: Participantsmentioning
confidence: 99%
“…In the Army, the fitness-for-duty testing is based on the MRT160, which is a slightly different version of the MRT test used in this study. The MRT is the standard test in the military for evaluating communication systems, and previous research has shown that performance on the MRT is correlated with the ability to understand operationally-relevant speech signals (Brungart et al, 2023) and to perform militarily relevant tasks (Garinther et al, 1995).…”
Section: Implications For Auditory Fitness-for-duty and Operational R...mentioning
confidence: 99%
“…One end of the "listen only" acoustic tube is connected to the narrow opening (6) using a simple passive adaptor (see Figure S1), while the other end is connected to the audio output of a voice tactical radio, for example, a personalized networking radio such as Elbit Systems-Land and C 4 ™ PNR-1000™. The second component added within tube (4) is a small noise filter (7) used to provide further sound attenuation before passing through narrow tube (3). Such a small noise filter was suggested by Berger and Hamery [23] to change sound attenuation behavior as is the case with the "Institute Saint Louis (ISL) filter" in the 3M™-Combat-Arms™4.1 earplug.…”
Section: Pcep Designmentioning
confidence: 99%
“…Such signals need to be heard clearly; hence, hearing acuity is a critical component of combat effectiveness and mission success [1,2]. In this context, Brungart et al [3] recently developed an evidence-based military auditory fitness-for-duty standard based on the 80-word modified rhyme test (MRT). This criterion was based on minimum speech intelligibility requirements that have been established for military communications equipment used by listeners with normal hearing.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we conduct a retrospective analysis of several datasets collected by our group that are well suited to examine potential interactions between aging and one dimension of linguistic experience: listeners' status as NNE or NE. Our group has conducted several large-scale studies of auditory function among United States Service Members (SMs; Brungart et al, 2019Brungart et al, , 2023K. W. Grant et al, 2021).…”
mentioning
confidence: 99%